Abnormal Liver Function Test in a Patient with Polymyalgia Rheumatica. (September 2014) - Ng, Choon Ta; Khoo, Ivan Yi; Boo, Ho Chin; Tulsidas, Haresh
Polymyalgia rheumatica is characterised by pain and stiffness of neck muscles, shoulder and pelvic girdles that is worse in the morning, generally accompanied by constitutional symptoms and an elevated erythrocyte sedimentation rate. Abnormal liver function is uncommonly associated with polymyalgia rheumatica. We describe a case of an elderly lady with polymyalgia rheumatica who presented with a history of early morning stiffness and pain in the lower limbs and markedly deranged liver function. She responded remarkably well to corticosteroid therapy with rapid improvement in her symptoms and normalisation of her liver function test.